Gambaran Kepatuhan Ibu dalam Pemberian Imunisasi Dasar Lengkap pada Anak Usia 12-18 Bulan di Wilayah Kerja Puskesmas Padang Pasir Tahun 2025 - Saputri, Melda; Nofrianti (Jurnal Kesehatan Lentera 'Aisyiyah, 2025)
Based on 2023 city health office data, the Padang Pasir Community Health Center recorded the lowest achievement of complete basic immunizations at 40.5% (291 infants), far below the 100% target. This study aimed to describe maternal compliance in providing complete basic immunizations to children aged 12–18 months in the Padang Pasir Health Center work area in 2025. The research was descriptive, conducted from May 23 to June 05, 2025, with 65 respondents selected using stratified sampling. Data were analyzed using univariate methods. Results showed that most respondents were under 35 years old (69.2%), worked as housewives (90.8%), and had a high school education (61.5%). More than half of mothers (60.0%) were compliant in providing complete basic immunizations to their children. The findings highlight the need for mothers to pay closer attention to their children’s immunization status and consistently bring them to health services. Community health centers are encouraged to strengthen collaboration with cadres to improve immunization coverage. Importantly, children under 18 months can still catch up on missed basic immunizations, emphasizing the importance of timely action to ensure optimal child health outcomes